Associations of Pet Ownership with Health and Wellbeing in Community Dwelling Adults aged 50 years and over in Ireland - Kenny, Rose; Mc Garrigle, Christine (My University, 2019)
Almost half (45%) of adults aged 50 years and over in Ireland own a pet with dogs being most common (38%) followed by cats (21%). Dog ownership decreases with increasing age from 51% of adults aged 50-64 years to 25% of those aged 75 and over. Almost two-fifths (38%) of dog owners walk their dog every day. Regardless of age, four of every five women report walking their dog at least three times per week, however only 67% of men aged 50-64 years do so compared to 84% of men aged 65- 74 years which may be due to work commitments. Dog owners are more likely to report high levels of physical activity (33%) compared to non-pet owners (24%) and those who own other pets (22%); dog owners who report regularly walking their dogs also report higher physical activity levels. • Three-fifths (58%) of dog owners report achieving the target 150 minutes per week of walking, compared to 51% of those with no pets and 45% of those with other pets. • While rural dwellers are twice as likely to have a dog compared to those in Dublin (49% versus 26%), rural dog owners are less likely to achieve the target minutes walking compared to those in Dublin or other towns/cities (53% versus 64-67%). Female dog owners are more likely to report being current smokers, however those who walk their dogs regularly have lower body mass index compared to non-regular dog walkers. • Dog owners have higher hand grip strength compared to adults who do not own any pets (28.7 versus 26.6 kg). Grip strength is a marker of muscle strength and frailty. • Dog owners who walk their dog at least three times a week are more likely to report active and social leisure activities in the past month (92% versus 86%) and close social relationships (44% versus 27%) than dog owners who walk their dog less frequently. The higher close social relationships among regular dog walkers is particularly evident for men. The reason for owning a pet is an important factor in explaining different mental health and wellbeing outcomes associated with dog ownership. While pet owners who report having a pet because they love animals have a higher sense of purpose in life, those who have a pet to keep busy or to have something to take care of, have lower wellbeing scores. It is important to consider the potential benefits of exposure to and interactions with pets and consequently, how to facilitate older adults to keep pets for as long as they wish to do so.
PUBLISHED
doi:https://www.doi.org/10.38018/TildaRe.2019-01
Keywords: Ageing